2007
DOI: 10.1363/3309807
|View full text |Cite
|
Sign up to set email alerts
|

HIV Risk Perceptions and First Sexual Intercourse Among Youth in Cape Town South Africa

Abstract: International Family Planning Perspectives, 2007, 33(3):98-105

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
53
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(65 citation statements)
references
References 33 publications
(67 reference statements)
11
53
1
Order By: Relevance
“…The lower perception of risk among those who were dating may be explained by the trust, as this appeared in studies with other populations, associated with feelings of invulnerability (Albuquerque et al 2010;Oltramari & Camargo, 2010). It was also observed that the adolescents underestimate their own risk in comparison with their peers, indicating that AIDS is seen as a disease of the other, a possibility projected in the exterior world, as found in other studies (Anderson et al, 2007;Camargo et al, 2010;Mwale, 2008).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…The lower perception of risk among those who were dating may be explained by the trust, as this appeared in studies with other populations, associated with feelings of invulnerability (Albuquerque et al 2010;Oltramari & Camargo, 2010). It was also observed that the adolescents underestimate their own risk in comparison with their peers, indicating that AIDS is seen as a disease of the other, a possibility projected in the exterior world, as found in other studies (Anderson et al, 2007;Camargo et al, 2010;Mwale, 2008).…”
Section: Discussionsupporting
confidence: 57%
“…Referring directly to the young, studies indicate that they tend to underestimate their risks of infection by HIV and to overestimate the risks of their peers (Anderson, Beutel, & Maughan-Brown, 2007;Mwale, 2008). In addition, aspects of peoples' relationships can influence their perceptions of risk in relation to HIV.…”
mentioning
confidence: 99%
“…The lower retention rate amongst whites is typical of survey research in South Africa, and is thought to be related to a higher rate of moving out of the area and higher opportunity costs involved in completing the questionnaire (Anderson, Beutel & Maughan-Brown, 2007). For a complete details of sampling methodology, non-response and attrition rates, see Lam, Seekings and Spark (2006).…”
Section: Methodsmentioning
confidence: 99%
“…11,12 Previous studies that examined the timing of first sexual intercourse among youth, including our own work, have focused largely on individual-level variables. [13][14][15][16] Although a few studies have acknowledged the relevance of structural and community variables, they have rarely established empirical connections between these variables and sexual debut. 4,[17][18][19] This study, which applies multilevel discrete-time hazard models to data collected from youth in Nyanza, fills an important research gap by examining the association of both individual-level and school-and community-level variables with the timing of first sexual intercourse.…”
mentioning
confidence: 99%
“…4,12,42 Such counterintuitive findings may largely be a result of the contemporaneous nature of the data, which makes it difficult to establish temporal order between variables that have reciprocal relationships; 4,16,25 longitudinal data are better suited for disentangling these complex, potentially causal connections. 13,16,26 Communication with relatives about AIDS might be expected to lead to positive behavioral outcomes, including delay of sexual initiation. In Sub-Saharan Africa, parentchild communication about sex (including the risks that HIV poses) is relatively uncommon; when it does occur, it often is the result of the parent discovering that the adolescent is sexually active, 43 which may explain the positive relationship between communication and sexual behavior in our analysis.…”
mentioning
confidence: 99%